"The Effectiveness of the Assure Learning Model Assisted by Audio-Visual Media on Digital Literacy and Conceptual Understanding of Mathematics in Students at SMP Negeri 4 Bolo" - Nur Amaliah; Lisda Ramdhani; Hardyanti Hardyanti; Ardi Rahmawan (Jurnal Ilmiah Mandala Education (JIME), 2025)
Introduction: The rapid evolution of digital technologies in the Industrial Revolution 4.0 and Society 5.0 eras necessitates that students develop strong digital literacy skills alongside a deep comprehension of mathematical principles. This research examines the efficacy of the ASSURE instructional model, enhanced by audiovisual resources, in boosting digital literacy and conceptual grasp of fractions for students at SMPN 4 Bolo.Material and Methods: This research adopted a quasi-experimental approach utilizing the Nonequivalent Control Group Design, which included 40 seventh-grade students (20 in the experimental group and 20 in the control group). The experimental group participated in instruction through the ASSURE model enhanced by audiovisual materials, whereas the control group followed standard traditional methods. Data collection tools comprised a digital literacy survey (reliability ?=0.82) and a test evaluating mathematical concept comprehension (?=0.85). The analysis of data incorporated descriptive statistics, an independent samples t-test, and N-gain computations via SPSS version 26.0.Research Results: The experimental group exhibited a substantial improvement in digital literacy, rising by 26.2 points (mean pretest=52.3; mean posttest=78.5), in contrast to the control group's modest gain of 9.4 points (mean pretest=51.8; mean posttest=61.2). Regarding mathematical conceptual understanding, the experimental group advanced by 33.6 points (mean pretest=48.7; mean posttest=82.3), whereas the control group progressed by just 14.3 points (mean pretest=49.2; mean posttest=63.5). Results from the independent samples t-test confirmed notable differences (p<0.05), supported by high effect sizes (Cohen's d=2.63 for digital literacy; d=2.89 for conceptual understanding). Furthermore, the N-gain assessment indicated that the experimental group attained a moderate level (g=0.55 and g=0.65).Conclusion: The ASSURE learning model assisted by audio-visual media proved effective in significantly improving students' digital literacy and mathematical conceptual understanding. This study contributes theoretically to the integration of digital literacy with mathematical conceptual understanding, and practically to teachers in designing innovative technology-based learning that meets 21st-century educational demands.